Identification Analysis of Fluid Type in the Low Resistivity Zone of Well Z-2 Field "Z", South Sumatera - Sigit Rahmawan; Firman Herdiansyah; Suryo Prakoso; Muhammad Burhannudinnur; Syamsul Irham; Samsol; Muhammad Himawan Prakoso; Hayafa Fakhriyatul Ummah (Journal of Earth Energy Science, Engineering, and Technology, 2023)
Hydrocarbon reserves are one of the main points that are very important in the sustainability of the productivity of an oil and gas field. This important point is greatly influenced by several parameters that can be obtained by various measurements and analysis. One of the most influential parameters in the analyses of the amount of hydrocarbon reserves in a reservoir is the water saturation value. The water saturation parameter will also be greatly influenced by the electrical parameters of the fluid-containing rock in the reservoir. Sometimes the electrical parameters of this rock, in this case resistivity becomes one of the benchmark parameters, whether the zone or reservoir has potential or is interesting to be developed or produced. However, there are several reservoirs or zones that experience low resistivity effects which will give an initial indication that the zones or reservoirs are not attractive or have no effect on development. In this Z field, there is a zone that experiences low resistivity effects, making this zone unattractive for production. So to be able to make these zones attractive for production, an identification analysis was carried out on Zones A and B in this Z field to determine the type or type of fluid from the two zones. The initial analysis was carried out petrographically from rock sample incisions at certain depths in Zones A and B so that it is known that the cause of the low resistivity effect in the two zones is the presence of pyrite minerals and illite clay which are the main causes of the low resistivity effect. Furthermore, an analysis of the identification of fluid types was carried out using the double apparent resistivity method with the results obtained that in Zones A and B there are 2 types of fluids, namely hydrocarbons and water with a depth limit of 3650 ft in Zone A and 4558 ft in Zone B. By knowing the type of fluid, the hydrocarbons contained in these two zones should be able to increase interest in the production of these zones as a potential zone for production, but it is necessary to perforate at a depth range indicated by the hydrocarbon fluid and carry out initial production tests to prove the results of the analysis in this study.